Analysis of melatonin and serotonin from cherries: a review - Varga-Visi, Éva; Jócsák, Ildikó; Lóki, Katalin; Végvári, György (Acta Agraria Kaposváriensis, 2018)
The proper quantification of serotonin and melatonin in different foods is indispensable to evaluate the significance of their dietary intake on blood and plasma levels in humans. This review summarizes the issues regarding the measurements of these compounds from sour cherry and sweet cherry. Sample preparation and analytical methods are discussed, mainly focusing on the liquid chromatographic determination of these compounds, with special respect to their parallel determination in one run.
Keywords: indoleamine derivatives; LC-MS; electrochemical detection; fluorometric detection